Analysis of Environmental Sanitation Risk Factors Scabies in Adolescents - Mely Gustina; Epti Yorita (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Scabies is an infectious disease that affects all races and groups worldwide but is more common in children and young adults. Meta-analysis found that occupancy density, temperature, light, clean water, ventilation, gender, personal hygiene, knowledge, and contact with sufferers were risk factors for scabies in adolescents living in Islamic boarding schools. Research is needed by identifying close contact cases in the community, especially in high-risk groups such as students who live in dormitories. This study aims to analyze the factors associated with the incidence of scabies in young women at the Makrifatul Ilmi Islamic Boarding School, South Bengkulu Regency. The research design was cross-sectional, with the dependent variable being knowledge, age, personal hygiene, and environmental sanitation, while the dependent variable was the incidence of scabies. A sample of 50 teenagers was taken by accidental sampling technique. Data collection was carried out using a questionnaire and an observation sheet. Data were analyzed univariately with frequency distribution tables, bivariate with chi-square, and multivariate logistic regression. The study's results found a relationship between gender and scabies, p=0.00, and there was a relationship between knowledge and scabies, p=0.00. There is a relationship between personal hygiene and scabies p=0.00. There is a relationship between environmental sanitation and scabies p=0.00. Environmental sanitation is the most dominant risk factor associated with scabies. Health service providers must work with non-health workers, including pesantren supervisors, parents, health workers, and health cadres, in conducting education, prevention, and treatment to ensure mite elimination and break the transmission.Keyword: Sanitation, Personal hygiene, Scabies knowledge